What to do about national defense. - Cohen, Eliot A. (Commentary)
Focuses on the need for the United States to rethink its national defense policy in view of a new strategic environment. Three dominant characteristics of the new strategic environment; Emergence of four missions for the armed forces; Choices for the government; Issue of civil-military relations.